Innovation in mental health care: Bertram Mandelbrote, the Phoenix Unit and the therapeutic community approach. Issue 1 (March 2023) - Millard, David; Agulnik, Peter; Armstrong, Neil; Fees, Craig; Hall, John; Kennard, David; Leach, Jonathan
Bertram Mandelbrote was Physician Superintendent and Consultant Psychiatrist at Littlemore Hospital in Oxford from 1959 to 1988. A humane pragmatist rather than theoretician, Mandelbrote was known for his facilitating style of leadership and working across organisational boundaries. He created the Phoenix Unit, an innovative admission unit run on therapeutic community lines which became a hub for community outreach. Material drawn from oral histories and witness seminars reflects the remarkably unstructured style of working on the Phoenix Unit and the enduring influence of Mandelbrote and fellow consultant Benn Pomryn's styles of leadership. Practices initiated at Littlemore led to a number of innovative services in Oxfordshire. These innovations place Mandelbrote as a pioneer in social psychiatry and the therapeutic community approach.